Visual search by training efficient and effective deep network models - Khaing, Phyu Thwe Htet Htet (2019)
This paper presents some of the state-of-the-art deep learning and machine learning methods for scene text detection and text recognition. It illustrates the performance and methods used in these novel solutions and analyze them for visual search problem in the area of natural scene text extraction problem.